Reimagining Chinese American Identity: Postcolonial Perspectives on Cultural Negotiation and Transformation in Laurence Yep’s Dragonwings (KEMANUSIAAN The Asian Journal of Humanities, 2023)
The Chinese immigrant and Chinese American communities have faced a long history of stigmatisation and misrepresentation due to racial bias and discrimination. This article explores the transformative growth narrative of the child protagonist in Laurence Yep’s novel Dragonwings, set against the backdrop of historical anti-Asian sentiment in the early 1900s. By adopting Said’s “imaginative geography” and Bhabha’s “third space” as analytical perspectives, the study aims to shed light on how the child protagonist’s growth challenges passive Chinese stereotypes and confronts deeply ingrained adversities within the Asian American diaspora by offering an active anti-Oriental perspective. We argue that the transformative journey of the protagonist, Moon Shadow, contests racial biases and cultural boundaries, contributing to a reflective perspective that liberates writers of colour from complicit interrogations. The analysis underlines the transgressive aesthetic within the Chinese American diaspora, showcasing Dragonwings as a quintessential postcolonial bildungsroman that embraces compromise and accommodation in selfformation. Furthermore, the exploration of the child protagonist’s growth in the context of historical realist narrative and the postcolonial lens emphasises the transgressive enjoyment that subverts established norms and identities. The study thus acknowledges the resilience and agency exhibited by the characters in the face of adversity and by understanding the emancipatory potential of growth narratives, it contributes to the broader theme of overcoming adversity and embracing change in the context of language and culture in Asia.